Melodic structure and inner self in clinical improvisation - Liarmakopoulou, Ourania (2016)
This study investigates the analogies between the melodic evolution within clinical improvisation and the shifts in the core self, across the continuum of music therapy process. This investigation is facilitated by a hypothesis; that musical shifts in improvisation’s structure precede psychological shifts in improviser’s self during therapy. Melodic improvisations created within the Integrative Improvisational Music Therapy (IIMT) model (Erkkilä, 2016) are investigated as proposed in the Therapeutic Narrative Analysis (Aldridge & Aldridge, 2008): certain melodic episodes from significant improvisations are analyzed with the Repertory Grid Method (Kelly, 1995) and patterns of the musical data demonstrate the client’s melodic evolution. The therapeutic themes traced in other sources of data (i.e. text transcripts, diaries) are connected with client’s musical development via the Theory of Analogy (Smeijsters, 2005). Results reveal analogies between the melodic evolution and the development of therapeutic themes across the therapeutic continuum. They also confirm the initial hypothesis: the very long improvisation where the client explores almost the whole range of her melodic potentiality precedes the session where she detects and expresses the source of her distress. These results further manifest clinical improvisation’s therapeutic potentiality and effectiveness within individual music therapy. Additionally, this study proposes a more musicological approach within an arbitrary musical analysis; to rather utilize musical terms than metaphors in describing the musical performance, thus presenting the musical meaning instead of interpreting it.